The factors that causes upper gastrointestinal hemorrhage - Hülya ÇETİNKAYA and İrfan SOYKAN and Ali Reşit Beyler and Necati ÖRMECİ and Ali GÖREN and Nihat SİPAHİ and Erol KESİM and Negüz SÜMER and Ali ÖZDEN and Kadir BAHAR and et al. (Turkish Journal of Gastroenterology, 2020)
-